Napisz nastepujące wyrażenia bez nawiasów i oblicz ich wartość:
a-5 + (-12) - 37 + 44 - (-18) + (-4)=
b)- 1/2 + (-1/4) - (-1/6) + (-1/8)=
c) 2,4 - (-7,2) + (-3,6) +4,7- (-5,5)+
d) -[-(-4,5)] + (-24,6) + 13,8 + (-22,3)=
e)-0,125 + 17/20 - (0,05) - (-5/16)=
f) 0,4 + (-1/5) -(-5,8) -6 1/2 +8,5=

3

Odpowiedzi

  • Użytkownik Zadane
2010-01-24T14:36:16+01:00
A) -5 -12 - 37 + 44 +18-4=
b)- 1/2-1/4 +1/6-1/8=
c) 2,4 +7,2-3,6 +4,7+5,5=
d) -4,5 -24,6 + 13,8 -22,3=
e)-0,125 + 17/20 - 0,05+5/16=
f) 0,4 -1/5+5,8 -6 1/2 +8,5=
3 2 3
  • Użytkownik Zadane
2010-01-24T14:39:21+01:00
A)-5 + (-12) - 37 + 44 - (-18) + (-4)= 4
b)- 1/2 + (-1/4) - (-1/6) + (-1/8)= - 40/48
c) 2,4 - (-7,2) + (-3,6) +4,7- (-5,5)= 16,2
d) -[-(-4,5)] + (-24,6) + 13,8 + (-22,3)= -37,6
e)-0,125 + 17/20 - (0,05) - (-5/16)= 79/80
f) 0,4 + (-1/5) -(-5,8) -6 1/2 +8,5= 8
2 3 2
Najlepsza Odpowiedź!
2010-01-24T14:41:42+01:00
A) -5 + (-12) - 37 + 44 - (-18) + (-4)= -5 -12 -37 +44+18 -4= 4
b) -1/2 + (-1/4) - (-1/6) + (-1/8)=-1/2 -1/4 +1/6 -1/8= -17/24
c) 2,4 - (-7,2) + (-3,6) +4,7- (-5,5)= 2,4 +7,2 -3,6 +4,7 +5,5= 16,2
d) -[-(-4,5)] + (-24,6) + 13,8 + (-22,3)= -4,5 -24,6 +13,8 -22,3= -37,6
e) -0,125 + 17/20 - (0,05) - (-5/16)= -1/8 +17/20 -1/20 +5/16= 79/80
f) 0,4 + (-1/5) -(-5,8) -6 1/2 +8,5= 0,4 -0,2 +5,8 -6,5 +8,5= 8
6 4 6